Persepsi Guru Pendidikan Agama Islam terhadap Penggunaan Artificial Intelligence (AI) sebagai Media Pembelajaran di Kota Medan - Muti Husnul Khotimah; Dini Febria Arifina; Rizky Arafani Nurhikmah Marpaung; Oktrigana Wirian (Yayasan Haiah Nusratul Islam, Indonesia, 2026)
Advances in Artificial Intelligence (AI) technology offer new opportunities to improve the quality of learning, including in the subject of Islamic Religious Education (PAI). This study aims to determine the perceptions of PAI teachers regarding the use of AI as a learning medium in the city of Medan. This study employs a quantitative approach using a descriptive survey method. The research subjects consisted of 30 PAI teachers selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using percentages. The results indicate that the majority of teachers hold positive perceptions regarding the use of AI. Teachers view AI as relevant to current educational needs, capable of helping to improve the quality of PAI instruction, and supportive of increasing students’ interest in learning. However, AI still requires teacher guidance to ensure its use aligns with educational objectives.